Unwanted isolation: An obstacle to constructive interaction between oncology nurses and their patients - Amir Hossain Pishgooie; Jamileh Mohtashami; Foroozan Atashzadeh‐Shoorideh; Neda Sanaie; Ensieh Fathollahzadeh; Victoria Skerrett (Wiley, 2021)
Abstract Aim The current study was carried out to investigate the obstacles faced by oncology nurses in their interactions with their patients. Design This research is a descriptive qualitative study. Methods In this study, conventional content analysis was used for analysing the data collected from 26 oncology nurses. The participants were selected through purposive sampling. Semi‐structured interviews were used for collecting data. Data analysis was conducted with Elo and Kyngäs's approach. Results The results included three categories: "role conflict," "role overload" and "inefficient interaction," and 10 subcategories.